(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article analyzes innovative and modern approaches to human resource management. The use of technologies and new methods in the management process is of great importance in increasing efficiency, fully utilizing the potential of employees, and achieving the strategic goals of organizations. The article examines modern trends in human resource management worldwide and highlights their advantages through statistical data. It also analyzes research conducted in this area and its results.